Experimental and Modeling Study of Human Tympanic Membrane Motion in the Presence of Middle Ear Liquid - Zhang, Xiangming (J Assoc Res Otolaryngol, 2014)
Vibration of the tympanic membrane (TM) has been measured at the umbo using laser Doppler vibrometry and analyzed with finite element (FE) models of the human ear. Recently, full-field TM surface motion has been reported using scanning laser Doppler vibrometry, holographic interferometry, and optical coherence tomography. Technologies for imaging human TM motion have the potential to lead to using a dedicated clinical diagnosis tool for identification of middle ear diseases. However, the effect of middle ear fluid (liquid) on TM surface motion is still not clear. In this study, a scanning laser Doppler vibrometer was used to measure the full-field surface motion of the TM from four human temporal bones. TM displacements were measured under normal and disease-mimicking conditions with different middle ear liquid levels over frequencies ranging from 0.2 to 8 kHz. An FE model of the human ear, including the ear canal, middle ear, and spiral cochlea was used to simulate the motion of the TM in normal and disease-mimicking conditions. The results from both experiments and FE model show that a simple deflection shape with one or two major displacement peak regions of the TM in normal ear was observed at low frequencies (1 kHz and below) while complicated ring-like pattern of the deflection shapes appeared at higher frequencies (4 kHz and above). The liquid in middle ear mainly affected TM deflection shapes at the frequencies higher than 1 kHz.